Efficacy of Panchakarma therapy and lifestyle modification in essential hypertensive patients to reduce anti-hypertensive dependency - Naik, Minal; Patil, Tejal; Gond, Bipin (International Journal Of Community Medicine And Public Health, 2024)
Background: Anti-hypertensive drugs are associated with a plethora of adverse reactions which can lead to poor treatment adherence, increased morbidity and mortality rates, and significant economic burden. The blood pressure management program (BPMP) is an Ayurvedic treatment strategy that combines Panchakarma with diet management. Thus, the current study sought to assess the efficacy of the BPMP in essential hypertensive patients to reduce anti-hypertension dependency. Methods: A retrospective, observational, single-centre study was conducted between December 2018 and September 2023 in Maharashtra, India. Patients aged 30-75 years diagnosed with primary/essential hypertension regardless of gender participated in the BPMP and were included in the study. Follow-up was conducted after 90 days. Day 1 and day 90 data were compared. Results: A total of 59 patients were assessed. Daytime ambulatory blood pressure monitoring (ABPM) systolic blood pressure decreased (day 1: 123.71±11.83 mmHg and day 90: 123.12±12.36 mmHg), night-time ABPM systolic blood pressure decreased (day 1: 114.76±13.41 mmHg and day 90: 114.31±14.40 mmHg), daytime ABPM diastolic blood pressure decreased (day 1: 77.03±8.28 mmHg and day 90: 76.31±9.45 mmHg, and night-time ABPM diastolic blood pressure decreased (day 1: 69.53±8.32 mmHg and day 90: 68.42±8.85 mmHg). Nocturnal dipping decreased (day 1: 7.08±8.19 and day 90: 6.08±8.99). Dependency on allopathic medication also decreased. Conclusions: The Ayurveda-based BPMP effectively reduces blood pressure and dependency of allopathic medication. It also improves quality of life of patients diagnosed with primary/essential hypertension.